2017
DOI: 10.1007/s00421-017-3662-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recovery interval duration on the parameters of the critical power model for incremental exercise

Abstract: The linear [Formula: see text] model for ramp exercise represents a particular case (for t = 0 s) of a more general model, accounting for energy resynthesis following oxygen deficit payment during recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…3 a). This is in keeping with previous studies demonstrating an exponential recovery of W ′ as a function of W ′ (Skiba et al 2015 ; Vinetti et al 2017 ). However, when expressed as a percentage of W ′ recovery, this relationship disappeared in the trained group and was negative in the untrained group, i.e., those with the highest W ′ reconstituted the smallest fractional of W ′ during recovery (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3 a). This is in keeping with previous studies demonstrating an exponential recovery of W ′ as a function of W ′ (Skiba et al 2015 ; Vinetti et al 2017 ). However, when expressed as a percentage of W ′ recovery, this relationship disappeared in the trained group and was negative in the untrained group, i.e., those with the highest W ′ reconstituted the smallest fractional of W ′ during recovery (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…W′ rec1 and W′ rec2 were defined as W′ reconstituted during the first recovery and second recovery periods, respectively; the difference between W′ reconstitution during the first and second recovery periods was defined as ∆W′ rec . The W′ reconstitution time constant τ was calculated based on an exponential recovery of W′ (Vinetti et al 2017) using the natural logarithm Eq. 2: For pulmonary gas exchange parameters, errant breaths, defined where VȮ 2 differed from the local mean by ≥ 4 SD, were removed.…”
Section: Data Processingmentioning
confidence: 99%
“…Despite some previous findings about the effects of protocol (i.e. workload vs recovery ratio) on O 2max (Vinetti et al 2017 ), these findings reinforce previous data demonstrating that O 2max was independent of the protocol adopted across different incremental testing procedures (Bentley et al 2007 ; Billat et al 1996 ; Riboli et al 2017 ). The present outcomes are in line with previous literature, in which no differences in O 2max were observed between protocols in different populations, such as recreationally-active men (Kirkeberg et al 2011 ), physically-active young adults (Riboli et al 2017 ), semi-professional soccer players (Riboli et al 2021 ) and competitive middle- and long-distance runners (Billat et al 1996 ; Kuipers et al 2003 ).…”
Section: Discussionsupporting
confidence: 81%
“…Conversely, incremental continuous protocols (CP) last short overall duration and they have been shown as a valid and reliable method to determine O 2max despite the submaximal physiological adjustments cannot be reached as in DP due to increments in work rate faster than cardiorespiratory and metabolic adjustments (Riboli et al 2017 , 2021 ). Despite in some intermittent protocols with very low workload vs recovery ratio O 2max may not be reached (Vinetti et al 2017 ), previous studies using CP and DP showed that O 2max was found to be independent from the protocol adopted (Kuipers et al 2003 ; Riboli et al 2017 , 2021 ). Conversely, testing protocols with shorter stage duration may lead to higher V max (Riboli et al 2017 ; Kuipers et al 2003 ; Adami et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since muscle O 2 is related to muscle reduction [Pcr] (di Prampero and Margaria 1968 ; Meyer 1988 ), the faster [Pcr] is depleted, the faster the O 2 increases. Conversely, during the recovery phase (below CP), [Pcr] resynthesis and W ′ recovery follow an exponential trend (Meyer 1988 ; Ferguson et al 2010 ; Skiba et al 2012 , 2014 ; Jones and Vanhatalo 2017 ; Vinetti et al 2017 ). Indeed, when exercise generates a large depletion of [Pcr], the resynthesis rate is faster in the beginning of the recovery and it slows when approaching complete restoration.…”
Section: Introductionmentioning
confidence: 99%